Bond strength of tension lap-splices in full scale self-compacting concrete beams - Türk, Kâzim; Benli, Ahmet; Calayir, Yusuf (My University, 2008)
Twelve full-scale beam specimens (2000 × 300 × 200 mm) were tested in positive bending with the loading system designed to determine the effect of self-compacting concrete (SCC) and the diameter of reinforcement on bond-slip characteristics of tension lap-slices. The specimens of lap-splice series were tested with lap-spliced bars centred on the midspan in a region of constant positive bending. The splice length of the deformed bars was set at 310 mm in all beam specimens. This value was selected to develop a steel stress less than yield to ensure splitting mode failure in all beam specimens. The beams were cast with the 16 and 20 mm bars (the tension lap-splices) in the bottom position. The casting procedure was the same for all beams. Two types of concrete were used in the experimental programme, including normal concrete (NC), with a slump less than 68 mm, as the comparatively low-slump concrete, and SCC as an extremely high-workability concrete. The variables used in this study were the concrete type (SCC and NC) and reinforcing bar size (16 and 20 mm). It was found that as the diameter of the steel bar increased from 16 to 20 mm the bond strength decreased regardless of concrete type. Finally, although the compressive strength of concretes was almost the same and there were slight differences between the diameters of lap-spliced bars, the normalised bond strengths of the SCC mixes were about 4% higher than those of the NC mixes for both bar diameters, indicating that the reinforcing bar was completely covered by SCC due to its filling ability. © TÜBİTAK.
Keywords: Bond strength; Full-scale beam; Lap splice; Positive bending; Self-compacting concrete